Influence of intrathecal delivery of bone marrow-derived mesenchymal stem cells on spinal inflammation and pain hypersensitivity in a rat model of peripheral nerve injury - Schäfer, Sabrina (BioMed Central, 2014)
BACKGROUND: Multipotent mesenchymal stem (stromal) cells (MSCs) have been credited with immunomodulative properties, supporting beneficial outcomes when transplanted into a variety of disease models involving inflammation. Potential mechanisms include the secretion of paracrine factors and the establishment of a neurotrophic microenvironment. To test the hypothesis that MSCs release soluble mediators that can attenuate local inflammation, we here analysed the influence of MSCs on the activation of microglia cells, as well as on inflammatory parameters and pain behaviour in a surgical rat model of neuropathic pain. METHODS: We focussed on an experimental model of partial sciatic nerve ligation (PSNL), characterised by a rapid and persistent inflammation in the dorsal lumbar spinal cord where sensory inputs from the sciatic nerve are processed. Via indwelling intrathecal catheters, MSCs were repetitively grafted into the intrathecal lumbar space. Animals were evaluated for mechanical and thermal hypersensitivity over a period of 21 days after PSNL. Afterwards, spinal cords were processed for immunohistochemical analysis of the microglial marker ionized calcium-binding adapter molecule 1 (Iba1) and quantification of inflammatory markers in ipsilateral dorsal horns. We hypothesised that injections on postsurgical days 2 to 4 would interfere with microglial activation, leading to a reduced production of pro-inflammatory cytokines and amelioration of pain behaviour. RESULTS: PSNL-induced mechanical allodynia or heat hyperalgesia were not influenced by MSC transplantation, and spinal cord inflammatory processes remained largely unaffected. Indeed, the early microglial response to PSNL characterised by increased Iba1 expression in the lumbar dorsal horn was not significantly altered and cytokine levels in the spinal cord at 21 days after surgery were similar to those found in vehicle-injected animals. Grafted MSCs were detected close to the pia mater, but were absent within the spinal cord parenchyma. CONCLUSIONS: We conclude that intrathecal administration is not an appropriate route to deliver cells for treatment of acute spinal cord inflammation as it leads to entrapment of grafted cells within the pia mater. We propose that the early inflammatory response triggered by PSNL in the lumbar spinal cord failed to effectively recruit MSCs or was insufficient to disturb the tissue integrity so as to allow MSCs to penetrate the spinal cord parenchyma.